(untitled) - Mann, Prem S. (New Jersey, 2004)
Through four previous editions, Introductory Statistics has made statistics both interesting and accessible to a wide and varied audience. The realistic content of its examples and exercises, the clarity and brevity of its presentation, and the soundness of its pedagogical approach have received the highest remarks from both students and instructors. Now this bestseller is available in a new Fifth Edition.
Keywords: Statistics,Thống kê